Establishment Of An In Vitro Cell Culture System For Human Hepatitis B Virus - Wang, Suk Mei (2001)

(untitled)
The major obstacle in the study of HBV has been the inability to infect either animal model system in vivo or continuous cell lines in vitro due to strict virushost range and preferential attachment of the HBV envelope proteins onto the plasma membrane of human hepatocytes. The direct involvement of human annexin-V, a calcium dependent phospholipid - binding protein in the initial step of HBV infection has been reported. Over the last decade, various culture conditions with exogenous soluble factors have also been exploited to enhance HBV infection in vitro. The aim of this study was to establish an in vitro cell culture system that would continuously produce sufficient HBV by episomal replication. To facilitate the penetration and internalization of HBV, the expression of annexin V (A V) was